Letter from Mrs. Susannah Huckerby to James Curtis Booth - Huckerby, Susannah (1863)
Mrs. Sussanah Huckerby writes to James Curtis Booth (1810-1888) with a wish to have a daughter employed in the Mint. Booth notes on the letter "the small business of the Mint would rather warrant the discharge than selection of female hands."
Keywords: Booth, James Curtis, 1810-1888; Sexism; Mint of the United States; United States Mint